High‐Temperature‐Stable and Regenerable Catalysts: Platinum Nanoparticles in Aligned Mesoporous Silica Wells. Issue 10 (22nd August 2013) - Xiao, Chaoxian; Maligal‐Ganesh, Raghu V.; Li, Tao; Qi, Zhiyuan; Guo, Zhiyong; Brashler, Kyle T.; Goes, Shannon; Li, Xinle; Goh, Tian Wei; Winans, Randall E.; Huang, Wenyu
Abstract We report the synthesis, structural characterization, thermal stability study, and regeneration of nanostructured catalysts made of 2.9 nm Pt nanoparticles sandwiched between a 180 nm SiO2 core and a mesoporous SiO2 shell. The SiO2 shell consists of 2.5 nm channels that are aligned perpendicular to the surface of the SiO2 core. The nanostructure mimics Pt nanoparticles that sit in mesoporous SiO2 wells (Pt@MSWs). By using synchrotron‐based small‐angle X‐ray scattering, we were able to prove the ordered structure of the aligned mesoporous shell. By using high‐temperature cyclohexane dehydrogenation as a model reaction, we found that the Pt@MSWs of different well depths showed stable activity at 500 °C after the induction period. Conversely, a control catalyst, SiO2‐sphere‐supported Pt nanoparticles without a mesoporous SiO2 shell (Pt/SiO2), was deactivated. We deliberately deactivated the Pt@MSWs catalyst with a 50 nm deep well by using carbon deposition induced by a low H2/cyclohexane ratio. The deactivated Pt@MSWs catalyst was regenerated by calcination at 500 °C with 20 % O2 balanced with He. After the regeneration treatments, the activity of the Pt@MSWs catalyst was fully restored. Our results suggest that the nanostructured catalysts—Pt nanoparticles confined inside mesoporous SiO2 wells—are stable and regenerable for treatments and reactions that require high temperatures.